Henry Rowe Schoolcraft papers - Schoolcraft, Henry Rowe, 1793-1864.; Cass, Lewis, 1782-1866.; Johnston, John, 1762-1828.; Nicollet, J. N. (Joseph Nicolas), 1786-1843.; Schoolcraft, Henry Rowe, 1793-1864.; Schoolcraft, Henry Rowe, 1793-1864; Schoolcraft, Henry Rowe, Mrs.; Schoolcraft, Jane Johnston, 1800-1842.; Schoolcraft, Lawrence, 1757-1840.
Correspondence, journals, articles, books, manuscript magazines, poetry, speeches, government reports, Indian vocabularies, maps, drawings, and other papers reflecting Schoolcraft's career as a glass manufacturer in New Hampshire, New York, and Vermont; mineralogist on an exploring expedition in the Ozark Mountains; geologist on the Cass expedition to the Northwest Territory; leader of expeditions throughout the Great Lakes region; member of Michigan's legislative council; Indian agent at Sault Sainte Marie and Mackinac Island (Mich.); superintendent of Indian affairs for Michigan; ethnologist and author of works concerning the Iroquois of New York state and other Indians of North America including Algic Researches (1839); and compiler and editor of Historical and Statistical Information Respecting the History, Condition and Prospects of the Indian Tribes of the United States (1851-1857).
Also includes correspondence and other papers of Schoolcraft's wives Jane Johnston Schoolcraft and Mary Howard (Mrs. Henry Rowe) Schoolcraft; papers of Schoolcraft's father Lawrence Schoolcraft, father-in-law John Johnston, and friend Lewis Cass; and Joseph N. Nicollet's journal (1836) of an expedition to the sources of the Mississippi.
Correspondents include John Russell Bartlett, John C. Calhoun, Lewis Cass, Ramsay Crooks, James Duane Doty, Edward Everett, Joseph Henry, John Harrison Howard (brother-in-law), John Hulbert (brother-in-law), Washington Irving, George Johnston (brother-in-law), Richard B. Kimball, William S. Lee, Francis Lieber, Lucius Lyon, Stevens Thomson Mason, William McMurray (brother-in-law), Pliny Miles, John Gorham Palfrey, Ely Samuel Parker, Francis Parkman, Thomas Ritchie, Willett H. Shearman, Benjamin Silliman, William Gilmore Simms, C. C. Trowbridge, and Henry Whiting.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Rare Book and Special Collections Division.
Author, ethnologist, explorer, geologist, glass manufacturer, and Indian agent.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: American periodicals; Ethnology -- New York (State); Ethnology -- North America; Geology -- Northwest, Old; Glass manufacture -- New Hampshire; Glass manufacture -- New York (State); Glass manufacture -- Vermont; Indians of North America; Indians of North America -- Government relations; Indians of North America -- Languages; Indians of North America -- Michigan; Indians of North America -- New York (State); Iroquois Indians; Lewis Cass Expedition, 1820.; Mineralogy -- Ozark Mountains; Great Lakes Region (North America) -- Discovery and exploration; Mackinac Island (Mich.) -- History; Michigan -- Politics and government; Mississippi River -- Discovery and exploration; Northwest, Old -- Discovery and exploration; Ozark Mountains -- Discovery and exploration; Sault Sainte Marie (Mich.) -- History; Bartlett, John Russell, -- 1805-1886 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Cass, Lewis, -- 1782-1866 -- Correspondence; Crooks, Ramsay, -- 1787-1859 -- Correspondence; Doty, James Duane, -- 1799-1865 -- Correspondence; Everett, Edward, -- 1794-1865 -- Correspondence; Henry, Joseph, -- 1797-1878 -- Correspondence; Howard, John Harrison -- Correspondence; Hulbert, John -- Correspondence; Irving, Washington, -- 1783-1859 -- Correspondence; Johnston, George -- Correspondence; Kimball, Richard B. -- 1816-1892 -- Correspondence; Lee, William S., -- active 1841 -- Correspondence; Lieber, Francis, -- 1800-1872 -- Correspondence; Lyon, Lucius, -- 1800-1851 -- Correspondence; Mason, Stevens Thomson, -- 1811-1843 -- Correspondence; McMurray, William, -- 1810-1894 -- Correspondence; Miles, Pliny, -- 1818-1865 -- Correspondence; Palfrey, John Gorham, -- 1796-1881 -- Correspondence; Parker, Ely Samuel, -- 1828-1895 -- Correspondence; Parkman, Francis, -- 1823-1893 -- Correspondence; Ritchie, Thomas, -- 1778-1854 -- Correspondence; Shearman, Willett H., -- 1792- -- Correspondence; Silliman, Benjamin, -- 1779-1864 -- Correspondence; Simms, William Gilmore, -- 1806-1870 -- Correspondence; Trowbridge, C. C. -- 1800-1883 -- Correspondence; Whiting, Henry, -- 1788-1851 -- Correspondence; Authors; Ethnologists; Explorers; Geologists; Glass manufacturers; Indian agents